Effectiveness and toxicity of second-line actinomycin D in patients with methotrexate-resistant postmolar low-risk gestational trophoblastic neoplasia - Maestá, Izildinha [UNESP]; Nitecki, Roni; Desmarais, Cecilia Canedo Freitas [UNESP]; Horowitz, Neil S.; Goldstein, Donald P.; Elias, Kevin M.; Berkowitz, Ross S. (Elsevier, 2020)
Objectives: The purpose of this study was to evaluate both the outcomes and toxicity of second-line actinomycin D (ActD) chemotherapy in methotrexate (MTX) - resistant low-risk postmolar gestational trophoblastic neoplasia (GTN) with 5-day ActD versus pulsed ActD. Methods: This retrospective cohort study included patients with MTX-resistant low-risk postmolar GTN from 1974 to 2016. Second-line chemotherapy consisted of 5-day ActD (10–12 μg/kg per day for 5 days every 14 days) or biweekly ActD (1.25 mg/m2 every 2 weeks). Data on patient characteristics, disease presentation, treatment outcome, and toxicity were collected. Results: Sixty-eight MTX-resistant patients receiving ActD as second-line chemotherapy were identified (5-day ActD, 53 patients; pulsed ActD, 15 patients). No significant differences were observed in patient/disease characteristics and sustained remission (overall rate 72%) between second-line ActD regimens. Time to hCG remission was significantly faster (median 21 vs 47 days, p = .04) and required fewer treatment cycles (median 1 vs 2, p < .001) with 5-day ActD. Thrombocytopenia was only observed with 5-day ActD (64.6 vs 0%, p < .001). The frequency (60.4 vs 16.7%, p = .009) and severity (grade 3: 37.9 vs 0%, p = .045) of oral mucositis was significantly higher with 5-day ActD. Grade 2 alopecia was significantly more frequent (70.6 vs 16.7%, p = .02) with 5-day ActD. Conclusions: While 5-day ActD and pulsed ActD achieve comparable remission rates, due to its reduced toxicity, ease of administration, and patient convenience, pulsed ActD should be the treatment of choice for MTX-resistant postmolar low-risk GTN.
Keywords: Actinomycin D; Effectiveness; Low-risk gestational trophoblastic neoplasia; Second-line chemotherapy; Toxicity